2016
DOI: 10.5539/jas.v8n2p74
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Food Production in Nigeria: Implication for Food Security in Nigeria

Abstract: <strong></strong><p>Food production in Nigeria is largely dependent on natural environmental resources like rainfall, temperature and relative humidity. This study examined the impact of some of these climatic variables on food production in Nigeria from 1975 to 2010. Secondary time series data obtained from FAOSTAT (Food and Agriculture Organization statistics) and Nigerian Meteorological Agency were used for the study. The data were analyzed using some econometric tools such as Augmented Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 10 publications
0
18
0
2
Order By: Relevance
“…Similarly, food prices are usually low during harvest periods, but flooding alters this seasonal pattern by causing a rise in food prices as a result of crop failure, corroborating the findings of [48] flood events occur mostly between July and October, the harvest season for staples like yam in south eastern Nigeria in the study by [50] show that flooding has negative effects on food security in various aspects. [11] recommended that measures and actions that can assist to alleviate the Climate-smart agricultural practices must be implemented to ensure that agricultural productions are not affected by the occurrence of extreme events.…”
Section: Climate Change and Effects Of Extreme Events On Agriculture:mentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, food prices are usually low during harvest periods, but flooding alters this seasonal pattern by causing a rise in food prices as a result of crop failure, corroborating the findings of [48] flood events occur mostly between July and October, the harvest season for staples like yam in south eastern Nigeria in the study by [50] show that flooding has negative effects on food security in various aspects. [11] recommended that measures and actions that can assist to alleviate the Climate-smart agricultural practices must be implemented to ensure that agricultural productions are not affected by the occurrence of extreme events.…”
Section: Climate Change and Effects Of Extreme Events On Agriculture:mentioning
confidence: 99%
“…Climate can affect the quantities and types of food produced as well as production-related income. Similarly,[11] opined that the climate change phenomenon will affect agriculture in a number of ways including changes in rainfall pattern. It should be noted that there are more uncertainties in the prediction of the beginning of rainy season for farmers.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1% change in rainfall will lead to about 3.5% increase in agricultural output. Idumah et. al (2016) in their study also found that rainfall had positive relationship with agricultural output but in the short run.…”
Section: Presentation and Discussion Of Resultsmentioning
confidence: 99%